Challenges in Quality of Education in Higher Education Institutions (HEIs) of Pakistan - Zohaib Hassan Sain (ELITE Association Indonesia, 2023)
ABSTRACTThe purpose of this study is based on exploratory research to identify “Challenges in Quality of Education in HEIs of Pakistan”. The exploratory research approach is used to achieve the objectives of the study in less time and with inexpensive means. Pakistan is facing a lot of challenges in the education sector such as curriculum, few training institutions, corruption in education, teacher behavior, and less research work. The purpose of our research is to identify the major challenges in the educational sector in Pakistan which the educational sector is suffering for the last few years. The researcher used triangulation to carry out the reliability and validity of the data for results. So, to conduct this triangulation the researcher used questionnaires for the students, questionnaires for the teachers, and interviews with the management. . In this regard primary data was collected from the focused group of students using a sample of 100 questionnaires for each university were filled by the students of the selected five universities. The findings highlight the positive relationship of quality education with curriculum, few training institutions, corruption in education, teacher behavior, and less research work. These challenges caused restrictions in accomplishing competent teaching and learning with respect to quality education. Keywords: Curriculum; Corruption; Teacher’s Behavior; Research Work.